Pengaruh Promosi Terhadap Keputusan Pembelian Konsumen GrabFood (Studi di Kota Tasikmalaya) - Nopebrianti, Novi; Putri Ramadhani, Audry (Asosiasi Ahli Administrasi Indonesia, 2022)
Grab companies must be able to compete, because consumer needs are increasingly complex and in order to attract the attention of consumers. There are several factors that consumers consider when making a purchase on Grab, one of which is promotion. This study aims to determine how promotion influences the purchasing decisions of GrabFood consumers in Tasikmalaya City. This study uses a quantitative approach and data collection methods using a questionnaire with a sample of 158 respondents in the City of Tasikmalaya. The analytical technique used is reliability test, descriptive analysis test, correlation test, normality test, linearity test, simple linear regression test and coefficient of determination test using SPSS 25. Based on the results of data analysis, it can be concluded that there is a positive promotion effect on GrabFood customer purchasing decisions, this means that if the promotion is increased, the purchase decision will also increase.